Dynamic Full‐Field Imaging of Rupture Radiation: Material Contrast Governs Source Mechanism. Issue 1 (9th January 2023) - Aichele, J.; Latour, S.; Catheline, S.; Roux, P.
Abstract: In seismology, the rupture mechanisms of an earthquake, a glacier stick‐slip and a landslide are not directly observed, but inferred from surface measurements. In contrast, laboratory experiments can illuminate near field effects. The near field reflects the rupture mechanism but is highly attenuated in the case of real‐world surface data. We directly image the elastic wave‐field of a nucleating rupture non‐invasively in its near‐field with ultrasound speckle correlation. Our imaging yields the particle velocity of the full shear wave field at the source location and inside the 3D frictional body. We experimentally show that a strong bimaterial contrast, as encountered in environmental seismology, yields a unidirectional or linear force mechanism for pre‐rupture microslips and decelerating supershear ruptures. A weak contrast, characteristic for earthquakes, generates a double‐couple source mechanism for sub‐Rayleigh ruptures, sometimes preceded by slow deformation at the interface. This deformation is reproduced by the NF of a unidirectional force. Plain Language Summary: Earthquakes, avalanches, icequakes and landslides originate from a common process: rupture at a material interface. During a rupture, for example, when a landslide slips, a characteristic pattern of seismic waves is created. This pattern differs at the earth's surface and the rupture interface, which is the source of the seismic waves inside the earth. Usually scientists only measure the waves arriving at the surface and need to deduce the wave pattern inside the earth from the surface measurement. We build a laboratory experiment which enables us to film wave propagation around the rupture surface, as if we had a camera inside the material. We film waves emitted during and prior to a rupture. For a soft material on a hard surface, such as encountered in icequakes or landslides, a single force model better explains the observed wave pattern than the commonly used model of four distributed forces. The rupture moves faster than shear waves propagate which results in a supershear cone, the elastic equivalent to the acoustic Mach cone created by supersonic aircrafts. For two materials of similar hardness, such as encountered in earthquakes, the classic model of four forces better explains the ruptures, which travel at sub‐shear speed. Key Points: Noninvasive elastic near‐field laboratory observations reveal source mechanisms of micro‐slips, supershear and sub‐Rayleigh ruptures Strong material contrasts as encountered in glacier stick‐slip and landslides cause single force micro‐slips and supershear ruptures Weak contrasts, which are found in natural faults, show a double‐couple mechanism that is at times preceded by a slowly rising single force